On the Composition of the Distributions ${x^{\lambda} _+ \ln^m x_+}$ and ${x_+^{-1/\lambda}}$ - Fisher, B.; Kraiweeradechachai, T. (Sarajevo Journal of Mathematics, 2024)
Let $F$ be a distribution and let $f$ be a locally summable... 2000 Mathematics Subject Classification. 46F10